Influence of the Cardiomyocyte Circadian Clock on Cardiac Physiology and Pathophysiology. (June 2015) - Martino, Tami A.; Young, Martin E.
Cardiac function and dysfunction exhibit striking time-of-day-dependent oscillations. Disturbances in both daily rhythms and sleep are associated with increased risk of heart disease, adverse cardiovascular events, and worsening outcomes. For example, the importance of maintaining normal daily rhythms is highlighted by epidemiologic observations that night shift workers present with increased incidence of cardiovascular disease. Rhythmicity in cardiac processes is mediated by a complex interaction between extracardiac (e.g., behaviors and associated neural and humoral fluctuations) and intracardiac influences. Over the course of the day, the intrinsic properties of the myocardium vary at the levels of gene and protein expression, metabolism, responsiveness to extracellular stimuli/stresses, and ion homeostasis, all of which affect contractility (e.g., heart rate and force generation). Over the past decade, the circadian clock within the cardiomyocyte has emerged as an essential mechanism responsible for modulating the intrinsic properties of the heart. Moreover, the critical role of this mechanism is underscored by reports that disruption, through genetic manipulation, results in development of cardiac disease and premature mortality in mice. These findings, in combination with reports that numerous cardiovascular risk factors (e.g., diet, diabetes, aging) distinctly affect the clock in the heart, have led to the hypothesis that aberrant regulation of this mechanism contributes to the etiology of cardiac dysfunction and disease. Here, we provide a comprehensive review on current knowledge regarding known roles of the heart clock and discuss the potential for using these insights for the future development of innovative strategies for the treatment of cardiovascular disease.